13 million years of seafloor spreading throughout the Red Sea Basin - Nico Augustin; Froukje M. van der Zwan; Colin W. Devey; Bryndís Brandsdóttir (Nature Communications, 2021)
Here, based on earthquake data, vertical gravity gradient data and high-resolution bathymetry, the authors show that the Red Sea is not in transition from rifting to spreading as previously proposed. They instead suggest it to be a mature ocean basin in which continuous seafloor spreading began quasi-instantaneously along its entire length around 13 Ma ago.